Analysis of impacts of thermal shocks on mechanical properties of E-glass fiber reinforced polyester composites. (October 2021) - Jamshidi, Zahra; Hejazi, Sayyed Mahdi; Sheikhzadeh, Mohammad; Alirezazadeh, Azam
Glass fiber reinforced polyester composites are economic and high-performance composite materialsthat has gained a wide range of applications. Besides the developments in composites design, scientific studies addressing the consequences of thermal changes on the mechanical properties of fiber reinforced polymer composites(FRPCs) are scarce. Therefore, the main aim of the present work is to investigate the physical/mechanical properties of glass fiber reinforced polyester composites under thermal shocks. The effects of thermal cycle duration (2, 5 and 20 hours) on the porosity and mechanical properties (maximum stress, strain, elastic modulus and impact resistance) of polymeric composites reinforced by glass fiber, woven fabric and copper/silica nanoparticles (NPs) were investigated. The results exhibited that the porosity and mechanical properties changed obviously in long duration cycles, i.e., 20 hours. Major reduction trends were observed when the fabric reinforced samples were further reinforced by NPs. It was concluded that although NPs reduce porosity and pose filling effect in composite matrix, can also provide stress concentration locations. The composites reinforced by woven fabric and prepared by RTM method provide better mechanical properties. Moreover, after thermal shocks, the fibers within the composite structure formed curved shapes. Consequently, a reduction occurred at the elastic modulus of fibrous reinforced composites (fiber or fabric) after thermal cycles. Besides theelevated porositywas the predominant factor reducing elastic modulus, fiber deformation was also considered as a hidden factor which has never been discussed in previous research studies. A model of bicomponent structure was used to explain the effects of fiber deformation on elastic modulus of the FRPCs.